Practice of Itsbat Marriage Application in Cidokom Village, Rumpin Subdistrict, Bogor Regency - Septiani, Rina; Fauzi, Akhmad; Kusumawati, Ita Rahmania; Rizal, Muhammad; Sarnidasari (Research and Social Study Institute, 2022)
Registration of marriages is important for the creation of orderly administration, especially in the case of marriage certificates, other functions as well as one of the prerequisites for obtaining civil rights so as to avoid prejudice and misperceptions that can lead to legal records. One of the absolute competencies of the Religious Courts is itsbat marriages (nikah itsbat) which has the purpose of requesting marriage legalization so that it has legal force for couples who are married according to religion and do not yet have proof of a marriage certificate. This study has the aim of examining the submission of itsbat marriage in Cidokom Village, Rumpin District, Bogor. This community service uses the PAR method by planning observing then carrying out activities. Based on the results of the first research, Itsbat marriage is an application for marriage legalization that is submitted to the court to declare the marriage valid and has legal force based on Article 7 compilation of Islamic law. In accordance with the provisions above, itsbat marriage can only be filed through the Religious Courts, in the area where the applicant lives, not through the Office of Religious Affairs (KUA). Second, the legal consequences of holding foreign marriage constituencies are not much different from the legal consequences arising from marriages in Indonesia, namely the emergence of rights and obligations of husband and wife, rights and obligations of parents and their powers, guardianship rights and legal consequences that arise. others caused by marriage. This legal consequence arises when the registration of marriages on religious marriages is legal in the eyes of Indonesian law, namely by issuing a marriage certificate court decision in the form of a Marriage Certificate for marriages between husband and wife that have been carried out according to religion.